2020
DOI: 10.3390/ijns6030061
|View full text |Cite
|
Sign up to set email alerts
|

Dr. Louis Isaac Woolf: At the Forefront of Newborn Screening and the Diet to Treat Phenylketonuria—Biography to Mark His 100th Birthday †

Abstract: * Retired [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The idea of a diet as a possible treatment for PKU was not new, but discussions in the 1930s had questioned whether the presumed biochemical abnormality was the cause of the clinical features in PKU, and whether a nutritionally adequate diet could be produced if phenylalanine was removed [ 25 , 26 ]. In the early 1950s, Dr. Louis Woolf, a chemist at Great Ormond Street Hospital, London [ 7 , 27 ], tried supplementing the diet of two infants with PKU with glutamic acid, hoping to reduce their blood phenylalanine concentrations by increasing its excretion. Blood phenylalanine was not lowered and there was no benefit to the children’s development.…”
Section: Dietary Treatment Of Pku—the Prototypementioning
confidence: 99%
See 2 more Smart Citations
“…The idea of a diet as a possible treatment for PKU was not new, but discussions in the 1930s had questioned whether the presumed biochemical abnormality was the cause of the clinical features in PKU, and whether a nutritionally adequate diet could be produced if phenylalanine was removed [ 25 , 26 ]. In the early 1950s, Dr. Louis Woolf, a chemist at Great Ormond Street Hospital, London [ 7 , 27 ], tried supplementing the diet of two infants with PKU with glutamic acid, hoping to reduce their blood phenylalanine concentrations by increasing its excretion. Blood phenylalanine was not lowered and there was no benefit to the children’s development.…”
Section: Dietary Treatment Of Pku—the Prototypementioning
confidence: 99%
“…Bickel, Gerrard and Hickmans were awarded the John Scott Award for the discovery of the dietary treatment [ 48 , 49 ] ( Figure 7 ). In 2019, the International Society for Neonatal Screening awarded Dr. Louis Woolf a plaque to recognize his contribution [ 5 , 7 , 50 ].…”
Section: Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Følling concluded that this secondary metabolite was derived from dietary phenylalanine, and later the condition was lately named [ 16 ]. PKU was first treated through dietary control in the 1950s, and then, in 1963, population-based newborn screening using dried blood spot (DBS) testing was introduced to assess Phe concentration [ 17 ], enabling early diagnosis and initiation of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only treatment available for all PKU patients in the UK is a lifelong phe restricted diet. This diet was first conceptualised by Professor Isaac Woolf using casein hydrolysate treated with active carbon to produce a dietary supplement low in Phe [ 4 ]. Woolf worked with Dr Horst Bickel to treat the first patient with this diet at Birmingham Children's Hospital [ 5 ].…”
Section: Introductionmentioning
confidence: 99%